Exploring tactile surface sensors as a gesture input device for intuitive robot programming - Muxfeldt, Arne; Haus, Jan Niklas; Jingyuan Cheng; Kubus, Daniel (2016 IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA), 2016)
The lack of efficient and intuitive programming paradigms for industrial manipulators stands in the way of increasing the degree of automation in various industrial manufacturing environments. We approach this lack by exploring tactile surface sensors (TSS) enclosing the links of a manipulator as a gesture input device for intuitive robot programming. First, our low-cost tactile surface sensor is briefly presented. Subsequently, a preliminary gesture set is introduced and feature-based approaches for gesture recognition are addressed. Furthermore, the extraction of relevant parameters from the gestures as well as the integration of gesture input into our skill-based robot control architecture are outlined. Quantitative performance results based on a user study with 12 subjects and a set of 7 gestures show that even with a comparatively low spatial resolution of the sensor (20mm) average accuracies of over 90% can be obtained.